2007
DOI: 10.1177/0363546507304329
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength after Anterior Shoulder Stabilization

Abstract: Muscle strength recovered faster with an arthroscopic procedure than with an open procedure during the early postoperative periods, and strength was restored to the level of the unaffected side at 6 months postoperatively. In the group with open Bankart repairs, the muscle strength during forward elevation recovered slower than did external and internal rotation muscle strengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
(23 reference statements)
0
26
1
2
Order By: Relevance
“…5,10,13,18,21,37,41 Advancements in surgery favoring arthroscopic procedures have led to the current situation, where patients with a tendency toward recurrent shoulder Radiologic arthrosis was evaluated with standard radiographic projections. Clinical arthrosis was evaluated with the WOOS questionnaire in an additional 9 patients without radiography. )…”
Section: Discussionmentioning
confidence: 99%
“…5,10,13,18,21,37,41 Advancements in surgery favoring arthroscopic procedures have led to the current situation, where patients with a tendency toward recurrent shoulder Radiologic arthrosis was evaluated with standard radiographic projections. Clinical arthrosis was evaluated with the WOOS questionnaire in an additional 9 patients without radiography. )…”
Section: Discussionmentioning
confidence: 99%
“…The function subset (maximum score, 60) improved from a mean of 32 (range, 18-45) at the initial evaluation to a mean of 54 (range, 51-56) at discharge. At the initial physical therapy evaluation, the patients had a mean of 22 (range, 15-28) on the pain subset (maximum score, 30), and at discharge had a mean of 27 (range, [21][22][23][24][25][26][27][28][29]. The patients had a mean satisfaction subset (maximum score, 10) of 4 (range, 0-6) at the initial evaluation, 6 (range, 5-7) at discharge.…”
Section: 37mentioning
confidence: 99%
“…5,10,25,29 O'Neill 25 found that 56% of patients with arthroscopic Bankart repairs treated with physical therapy postoperatively exhibited strength deficits with isokinetic testing at a mean of 52 months postsurgery.…”
Section: 37mentioning
confidence: 99%
“…Os resultados do tratamento da luxação recidivante por via convencional, segundo a literatura, apresentam índices de recidivas que variam entre 3 e 8% dependendo do autor, sendo considerada ainda golden standard para essa lesão (2,5) . A artroscopia trouxe grandes avanços, como melhor conhecimento das lesões associadas, melhor estética, menor risco de falência do músculo subescapular, rá-pido retorno ao trabalho e esportes e alta satisfação do paciente (6,8,9,10) . Apresenta resultados semelhantes aos da cirurgia aberta quando uma adequada seleção do paciente é realizada (8,9) .…”
Section: Introductionunclassified